Antisense Transcripts and Antisense Protein: A New Perspective on Human Immunodeficiency Virus Type 1 - Savoret, Juliette; Mesnard, Jean-Michel; Gross, Antoine; Chazal, Nathalie (Frontiers in Microbiology, 2021)
It was first predicted in 1988 that there may be an Open Reading Frame (ORF) on the negative strand of the Human Immunodeficiency Virus type 1 (HIV-1) genome that could encode a protein named AntiSense Protein (ASP). In spite of some controversy, reports began to emerge some years later describing the detection of HIV-1 antisense transcripts, the presence of ASP in transfected and infected cells, and the existence of an immune response targeting ASP. Recently, it was established that the asp gene is exclusively conserved within the pandemic group M of HIV-1. In this review, we summarize the latest findings on HIV-1 antisense transcripts and ASP, we discuss their potential functions in HIV-1 infection together with the role played by antisense transcripts and antisense proteins in some other viruses. Finally, we suggest pathways raised by the study of antisense transcripts and proteins that may warrant exploration in the future.